American vista - "Acheson, Dean" (London, 1956)
This book covers the following topics Personal prologue; The oldest party is the youngest party; Modern Democracy- The Intertwined Strands:Conservatism and Empiricism; Modern Democracy in foreign affairs; Foreign Policy continued-The Underlying tasks; The state and the individual; The state and the Individual- A party position etc.
Keywords: U S A- Politics and government